2017
DOI: 10.18869/nirp.ijmtfm.7.3.145
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude of Medical Students of Cairo University, Cairo, Egypt About National DNA Database

Abstract: Background: DNA database is used to identify individuals based on their specific DNA profiles. In Egypt, a definitive law describing and legalizing DNA related issues is absent; however, the Egyptian courts frequently deal with these issues. The legal authorities strongly suggest the impending need for detailed decrees in this regard that guard the safety of the whole Egyptian community. This paper aimed to assess the knowledge and attitude of Medical students about Egyptian National DNA Database (END).Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Thus, the Criminal Law (Forensic Procedures) Amendment Act ( 2013) expressly provides a definition, obtaining, processing, and storing of DNA profiles in the Forensic DNA Database of South Africa (NFDD) [16,75,76,17]. In Egypt, there is no definitive legislative provision for the use of DNA evidence, obtaining, processing, and storing DNA profiling in the Egyptian National DNA Database (END) [75,77]. However, it is reported that the Egyptian courts have frequently dealt with forensic DNA evidence [77].…”
Section: Legislation and Regulation Of Forensic Dna Profiling/ Database In Africanmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the Criminal Law (Forensic Procedures) Amendment Act ( 2013) expressly provides a definition, obtaining, processing, and storing of DNA profiles in the Forensic DNA Database of South Africa (NFDD) [16,75,76,17]. In Egypt, there is no definitive legislative provision for the use of DNA evidence, obtaining, processing, and storing DNA profiling in the Egyptian National DNA Database (END) [75,77]. However, it is reported that the Egyptian courts have frequently dealt with forensic DNA evidence [77].…”
Section: Legislation and Regulation Of Forensic Dna Profiling/ Database In Africanmentioning
confidence: 99%
“…In Egypt, there is no definitive legislative provision for the use of DNA evidence, obtaining, processing, and storing DNA profiling in the Egyptian National DNA Database (END) [75,77]. However, it is reported that the Egyptian courts have frequently dealt with forensic DNA evidence [77]. for the rest of the enlisted African countries with reported DNA databases as demonstrated in figure 1, are yet to adopt specific and express legislative provision for their respective forensic DNA databases [75,44,28].…”
Section: Legislation and Regulation Of Forensic Dna Profiling/ Database In Africanmentioning
confidence: 99%
“…Also, there is a paucity of scientific report about the level of public awareness concerning forensic DNA database and the willingness for possible inclusion of DNA profiles in the National Forensic DNA Database in Africa particularly Nigeria. Hence our interest in assessing a sample of Nigerian adults on their knowledge and acceptance of a national forensic DNA database to support criminal investigation as conducted by other groups of researchers around the world in support of a responsible forensic DNA database policy [25,3,15,5,21].…”
Section: Introductionmentioning
confidence: 99%